miRNAs regulate stem cell self-renewal and differentiation - Yu, Zuoren; Li, Yuan; Fan, Huimin; Liu, Zhongmin; Pestell, Richard G. (Frontiers in Genetics, 2012)
Stem cells undergo symmetric and asymmetric divisions to generate differentiated cells and more stem cells. The balance between self-renewal and differentiation of stem cells is controlled by transcription factors, epigenetic regulatory networks and microRNAs. Herein the microRNA involvement in the regulation of stem cell self-renewal and differentiation is summarized. microRNA contribution to malignancy through regulating cancer stem cells are described. In addition, the reciprocal associations between microRNAs and epigenetic modifications in control of stem cell fate are discussed.